Information needs and sources of information among people with depression and anxiety: a scoping review - Chan, Frederick H. F. (2023)
Background: Previous studies have identified substantial unmet information needs in people with depression and anxiety. Sufficient information about the disorder, treatment, available services, and strategies for self-management is essential as it may influence quality of care and patients’ quality of life. This scoping review aimed to provide a broad overview of information needs of people with depression and anxiety as well as the sources that they use to seek this information. Methods: We included all primary research published in English that investigated information needs or information sources in people with depression or anxiety, with no restrictions imposed on the study design, location, setting, or participant characteristics. Six electronic databases (MEDLINE, Embase, PsycINFO, CINAHL, LISTA, Web of Science) and the grey literature (Google and Google Scholar) were searched for relevant studies published up to November 2021. Two reviewers independently screened articles and extracted data. Narrative synthesis was performed to identify key themes of information needs and information sources. Factors associated with information needs/sources such as demographic variables and symptom severity were also identified. Results: Fifty-six studies (comprising 8320 participants) were included. Information needs were categorised into seven themes, including general facts, treatment, lived experience, healthcare services, coping, financial/legal, and other information. The most frequently reported needs in both people with depression and anxiety were general facts and treatment information. Subclinical samples who self-reported depressive/anxious symptoms appeared less interested in treatment information than patients with clinical diagnoses. Information sources were summarised into five categories: health professionals, written materials, media, interpersonal interactions, and organisational resources. Health professionals and media (including the internet) were the most frequently adopted and preferred sources. Although few studies have examined factors associated with information needs and information sources, there is preliminary evidence that symptom severity and disease subtypes are related to information needs/sources, whereas findings on demographic factors were mixed. Conclusions: Information needs appear to be high in people with depression and anxiety. Future research should examine differences between subgroups and associated factors such as the treatment course. Personalised information provision strategies are also needed to customise information according to individual needs and patient profiles. Trial Registration: The protocol of this scoping review was registered on Open Science Framework (OSF; link: https://doi.org/10.17605/OSF.IO/DF2M6).